Globally Engaged Firms in the COVID-19 Crisis - Constantinescu, Cristina; Fernandes, Ana Margarida; Grover, Arti; Poupakis, Stavros; Reyes, Santiago (World Bank, Washington, DC, 2022)
This paper analyzes the initial impact and recovery of globally engaged firms from the COVID-19 crisis. It uses rich survey data of nearly 65,000 firm-year observations in 45 countries spanning three waves of data collection. The findings are organized in a series of stylized facts, which suggest that although the pandemic had an immediate adverse impact on most firms, the globally engaged ones are recovering faster, possibly due to their higher capabilities. Among globally engaged firms, those directly involved with international markets show better recovery than the ones that were indirectly involved. These results mask wide variation by firm traits, sectoral attributes, and country characteristics. At the core of the recovery of globally engaged firms is their heightened response to the crisis by finding novel ways to adapt supply chains even in the presence of lockdowns and uncertainty. These firms swiftly digitalized, introduced new products and changed their markets and sources of inputs. Over and above their capabilities, global engagement cushions firms against shocks. Policymakers could therefore facilitate global linkages by providing information on potential markets and products, by making production flexible in terms of facilitating remote work, reducing the rigidity of contracts; and incentivizing financial institutions to issue instruments that reduce uncertainty risk.